Perbandingan atau Pertandingan Agama-agama Ibrāhīmī? - Kautsar Azhari Noer (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2011)
This paper attempts to appreciate the work of an ex-priest who now is a Muslim author, Jerald F. Dirks, entitled Abrahamic Faiths. In the context of comparative religion studies, the writer (Kautsar Azhari)asks: is this Dirks’ work a comparison or competition of religions? Kautsar concludes that the work tends to be a competition in between the Abrahamic religions. However, the match was a friendly match. Dirks’ book, even though apologetic and polemical in character, is served in polite way and style, and is a work trying to reconcile between the children of AbrahamKeywords: God, theology, monotheism.DOI: 10.15408/ref.v13i1.990